RETRACTED Genome-wide analysis of the B-box gene family in the sweetpotato wild ancestor Ipomoea trifida and determination of the function of IbBBX28 in the regulation of flowering time of Arabidopsis - Dong, Jingjing (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.